A Donkey and His Voice in the Poetry of Zvane Črnja - Rudan, Evelina (Poznańskie Studia Slawistyczne, 2021)
A donkey is an animal that can be found in linguistic, literary, and cultural-anthropological works. However, this work analyses the symbolism of the animals that appear in the Chakavian poetry by Zvane Črnja, Croatian poet, opinion journalist and cultural historian. It specifically focuses on the character of donkey (or tovar) in that poetry, as well as the poetic effect of the place that the motif or the subject of donkey occupies in Črnja’s poems. In his poetry, the donkey represents, at least to an extent, a signum or a symbol of the rebellion of those who are oppressed, invisible or marginalized due to their language, their culture or their social status. It is a symbol of all of those who perceive their marginalism as the cause for uprising or newly awakened self-awareness, and which, in part, fits into the pattern of the Mediterranean cultural codex, due to its humoristic aspect.